O efekcie interpretacyjnego domina = About the interpretative domino effect - Ławski, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The issue of the paper is a phenomenon belonging to the theory of interpretative procedures.These procedures are practiced in humanities. The author notices that the unclear meaning of thetexts is very often caused by some reasons: 1) scholars use vague, ambiguous, figurative languageof discourse. In the case of the literary research it cases the accumulated ambiguity; 2) literarycommentators use the trains of associations; a text is in associations with another ones but its rightmeaning is blurred. The author of the study analyses this phenomenon using example of theoreticaldiscussion about "a problem of text" which had place in "Teksty Drugie" in 1998 year.
Keywords: literaturoznawstwo; literaturoznawstwo polskie; efekt domina (ED); 21 w.